Better governance and public policy : capacity building for democratic renewal in Africa - Olowu, Dele.; Sako, Soumana (Bloomfield, CT : Kumarian Press, 2002)
Governance is an important term in development policy discourse, yet its relationship to development, institutional reforms and public policy processes remains ambiguous. This book brings together analysis of these issues by scholars and practitioners of African development policy.
1. Introduction: Governance and Policy Management Capacity in Africa / Dele Olowu -- 2. Comparing Governance Across Countries and Over Time: Conceptual Challenges / Goran Hyden and Julius Court -- 3. On Common Good and Good Governance: An Alternative Approach / O.P. Dwivedi -- 4. Governance, Institutional Reforms, and Policy Processes in Africa: Research and Capacity-Building Implications / Dele Olowu -- 5. The Public-Private Sector-Interface -- The ACBF Perspective / Soumana Sako -- 6. The ACBF-PACT Model As a Best Practice Model for Capacity Building / Gene Ogiogio and Grace Ongile -- 7. Governance and Policy Analysis / Vasant Moharir -- 8. European Union Environmental Regulations and Their Potential Impact on Market Access for Africa's Exports / Paschal B. Mihyo -- 9. Environmental Governance, Policies, and Politics in Eastern and Southern Africa / M.A. Mohamed Salih -- 10. Policy Process in a Democratic Context: A Glimpse at Nigeria's Privatization Program / Ejeviome Eloho Otobo -- 11. Governance, Institutional Reforms, and Policy Outcomes in Ghana / Joseph Ayee -- 12. Economic Policy Research, Governance, and Economic Development: The Case of Namibia / Dirk Hansohm -- 13. Governance and Local Government Reforms in Zambia's Third Republic / Royson M. Mukwena and Peter K. Lolojih.
Includes bibliographical references and index.
Keywords: Since 1960; Democratization -- Africa; Political planning -- Africa; Nigeria